Respon Pertumbuhan dan Daya Tahan Hidup Setek Mikro Krisan - Gina Gustiani Pitaloka; Ai Komariah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2011)
The objectives of this experiment was to study the interaction between NAA and alginate concentrations on growth and shelf life of Chrysanthemum morifolium Rahmat Syn. Micro cutting in capsule. Design of this experiment used Randomized Block Design with two factors and two replication. The first factor wa concentration of NAA consisted of three levels (0.00 ppm, 0.10 ppm, and 0,15 ppm) and the second factor was concentration of alginate consisted of four levels (1.5%, 2%, 2.5% and 3.0%).the result of experiment showed that interaction among concentration of NAA and alginate on capsule texture, plant weight, leaves number, leaves weight, and shelf life of plant in capsule. There was no interaction between concentration of NAA and alginate on percentage of green capsules, percentage of micro cutting shoot growth, and percentage of capability of shoot growth break through capsule. Optimum concentration for plant weight was 0.1281 ppm NAA and 2.4671% alginate, with maximum weight was 0.0145 grams. Optimum concentration for shelf life of micro cutting in capsule was 0.1191 ppm NAA and 2.8071% alginate, with maximum shelf life was 5.9541 days.